2019
DOI: 10.3892/etm.2019.7839
|View full text |Cite
|
Sign up to set email alerts
|

The influence of PM2.5 on lung injury and cytokines in mice

Abstract: Exposure to particulate matter ≤2.5 µm in diameter (PM2.5) profoundly affects human health. However, the role of PM2.5 on lung injury and cytokine levels in mice is currently unknown. The aim was to examine the effect of PM2.5 pollution on lung injury in mice fed at an underground parking lot. A total of 20 female Kunming mice were randomly divided into control and polluted groups, with 10 rats in each group. The control group was kept in the laboratory, while the pollution group was fed in an underground park… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 62 publications
4
43
0
1
Order By: Relevance
“…Air pollution represents one of the most well-known causes of prolonged inflammation, eventually leading to an innate immune system hyper-activation. In a small cohort of mice exposed for three months to particulate matter 2.5 mm in diameter (PM 2.5 ), IL-4, TNF-a and transforming growth factor (TGF)-b1 were significantly increased in both serum and lung parenchyma, as well as leucocytes and macrophages (Yang et al, 2019). Obviously, a high systemic inflammation impairs heart function too, as witnessed in another cohort of mice exposed to PM 2.5 and PM 10 (Radan et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Air pollution represents one of the most well-known causes of prolonged inflammation, eventually leading to an innate immune system hyper-activation. In a small cohort of mice exposed for three months to particulate matter 2.5 mm in diameter (PM 2.5 ), IL-4, TNF-a and transforming growth factor (TGF)-b1 were significantly increased in both serum and lung parenchyma, as well as leucocytes and macrophages (Yang et al, 2019). Obviously, a high systemic inflammation impairs heart function too, as witnessed in another cohort of mice exposed to PM 2.5 and PM 10 (Radan et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…PM2.5 mainly contains 16 kinds of polycyclic aromatic hydrocarbons (PAHs) and metals, and excessive production of ROS is one of the key factors for PM2.5-induced cell damage. Our previous studies have shown that PM2.5 aggravates allergic asthma in mice by promoting inflammatory responses and inhibiting autophagy 39 . At the same time, we also found that PM2.5 promotes apoptosis and autophagy in alveolar epithelial cells through ROS/AMPK signaling 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study too, long-term exposure to PM 2.5 was associated with high systemic inflammation markers (CRP and LDH) and low FEV 1 % and D LCO among study populations. PM 2.5 and UFP induced inflammation at the alveolar epithelium level [26,27]. D LCO measurement is based on exchanged oxygen from the lungs into the blood at the level of the alveolar membrane and vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%